Sustainable manufacturing practice & sustainability performance: a case study in a semiconductor manufacturing company - Mohd Hisam, Nurfatin Nazwa; Hami, Norsiah (2018)
Sustainable manufacturing practice is one of the initiatives in manufacturing operations that need to be emphasized to preserve the natural environment and increase the quality of human life while doing business for economic values. Manufacturing companies need to implement sustainable manufacturing practice to solve or mitigate the issues of sustainability. The purpose of this paper is to explore the implementation of sustainable manufacturing practice in a selected manufacturing company. In specific, this study has been conducted to answer two research questions related to the types of sustainable manufacturing practice being implemented in the company studied and barriers or challenges to the implementation of sustainable manufacturing practice encountered by the company studied. Using a qualitative approach, a single case study analysis was conducted in this study. The data was collected through an interview session. The study discovers that there are various types of sustainable manufacturing practice that are implemented by the company studied such as substitution of non-environmental friendly materials and processes, using green technology, adopting paperless concept, as well as being socially responsible towards employees, suppliers, and customers. Two barriers or challenges to the implementation of sustainable manufacturing practice in the company studied i.e. lack of knowledge and expertise and cost. The findings of this study provide a good basis to understand the sustainable manufacturing practice and fundamental barriers to implementing such practices. Sustainable manufacturing practice may lead to better economic, environmental, and social sustainability.